Green Practices: A Solution for Environmental Deregulation and the Future of Energy Efficiency in the Post-COVID-19 Era - Khan, Kanwal I.; Nasir, Adeel; Rashid, Tayyiba (Frontiers in Energy Research, 2022)
The world has paid increasing attention to the energy efficiency project after the Paris agreement and UN climate summit. Recently, the COVID-19 pandemic accelerated the process of the green energy transition, which has attracted the considerable attention of economists, environmentalists, and international organizations and has led to significant research in energy. This study addresses the importance of green energy practices in the post-COVID era to deal with environmental deregulation using bibliometric analysis. Data were extracted from the Scopus database from 2020-to 2022. Results indicate that China gained a prominent place in publishing topic-related articles. However, Italy stands at the top position in total and average article citations. Sustainability is the most productive journal, followed by Energies and Journal of Cleaner Production. Nazarbayev University and the University of Cambridge are the most contributing research institutes. In general, the cooperation of authors, institutes, and countries strengthens the research; however, the collaboration at the author level across the nation was lower than the others. The study highlights three research streams and four themes by systematically conducting a bibliometric coupling and co-occurrence network that highly anticipate and significantly segregate the literature. Bibliometric coupling identifies three research streams of sustainable green business strategies, green infrastructure requirements and green solutions and opportunities from COVID 19. Furthermore, the co-occurrence network proposes four main themes related to green innovation in the epidemic era, security and sustainable development goals with green practices, public health protection and green finance, investment and risk management. The results are helpful to grasp the current research in the field of energy and assist in future research work to promote environmentally friendly projects.